Comparative Study of Engagement and Ring Exchange in Karampuang Village, Panakukang District, Makassar City: Perspective of Islamic Customs and Law - Abu Haif; Idrus Idrus; Nasrullah Nasrullah; Faisal Furqan; Askah Syahril (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This research aims to determine the factors that occur when Engagements and Ring Exchanges occur and how they are resolved in Karampuang Village as well as understanding more deeply the relevance of these settlements to Islamic law and KHI that apply in Indonesia. This is so that we can encourage people to realize the importance of knowing these customs in order to avoid undesirable things, both among intellectuals and among lay people. So what is used is a qualitative method which includes observation, as well as direct observation in the field. Furthermore, the results of this research show that there are several factors in the occurrence of customs of engagement and exchanging rings, and the most dominant or frequently occurring in the field is the factor when rings are worn between both parties and the factor of wearing gold rings for men. The traditional practice of engagement and exchanging rings in Karampuang Village is the procession of wearing a ring on the left ring finger using a gold ring, which is marked as a link between the two parties and is a symbol of someone's marriage proposal, with the aim of following the ring ceremony process. Islamic legal provisions regarding the tradition of exchanging rings in Karampuang Village need to be adjusted to Islamic law. Because the exchange of rings is a bond and this tradition also uses gold which is prohibited for men to wear, the solution that approaches Islamic rules for exchanging rings for the bride and groom is when the families of both parties take over. In this implementation, the bride is fitted with a ring by a woman from the man's family, for example. After reviewing several hadiths, almost all of them point to prohibitions, so the best solution is not to use a gold ring, the groom can replace it with a ring made of iron, because there is no prohibition